PEMBERDAYAAN MASYARAKAT KELURAHAN BENOA MELALUI PROGRAM KKN UNTUK MEWUJUDKAN MASYARAKAT YANG SEHAT DAN INOVATIF - M.A. Pratiwi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
The global COVID-19 pandemic has brought many changes, especially to the health conditions of the world community and economy. A very crucial impact in the province of Bali is the decline in public health and many family heads have lost their jobs. This resulted in a very significant decline in public health and welfare. The community of Benoa Village, Bali is one of the many villages experiencing a decline in health and welfare. One of the efforts that can be made to improve welfare is through the